2015
DOI: 10.1016/j.neuroimage.2015.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter density is associated with morningness–eveningness: Evidence from voxel-based morphometry

Abstract: Diurnal preference (morningness-eveningness) is known to be associated with several individual characteristics that are important in the fields of sociology, education, and psychiatry. Despite this importance, the anatomical correlates of individual differences in morningness-eveningness are unknown, and these were investigated in the present study. We used voxel-based morphometry and a questionnaire to determine individual morningness-eveningness and its association with brain structures in 432 healthy men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 102 publications
(132 reference statements)
2
23
2
Order By: Relevance
“…However, the fact that our study has a larger statistical power alone indicates that our finding is more reliable than other research in the field even when the reported P value is the same. Nonetheless, the lack of a strong (or midlevel) correlation between cognition and brain structures of any one area in analyses of a large sample of young adults is a widely seen phenomenon 39 62 63 64 . This phenomenon may suggest that at least in this group, it is difficult to reliably estimate cognitive differences from any one area of one brain image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that our study has a larger statistical power alone indicates that our finding is more reliable than other research in the field even when the reported P value is the same. Nonetheless, the lack of a strong (or midlevel) correlation between cognition and brain structures of any one area in analyses of a large sample of young adults is a widely seen phenomenon 39 62 63 64 . This phenomenon may suggest that at least in this group, it is difficult to reliably estimate cognitive differences from any one area of one brain image.…”
Section: Discussionmentioning
confidence: 99%
“…Preprocessing of the structural data was performed using Statistical Parametric Mapping software (SPM8; Wellcome Department of Cognitive Neurology, London, UK) implemented in Matlab (Mathworks Inc., Natick, MA, USA). Using a previously described method 39 involving a new segmentation algorithm implemented in SPM8, the diffeomorphic anatomical registration through exponentiated lie algebra (DARTEL) registration process implemented in SPM8, images were spatially normalized to the Montreal Neurological Institute (MNI) space to give images with 1.5 × 1.5 × 1.5 mm 3 voxels. Subsequently, all images were smoothed by convolving them with an isotropic Gaussian kernel of 12 mm full width at half maximum (FWHM) for the reasons described below.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to low effect size and statistical power, it is also possible that the multiple areas showing significant associations with CCA in different studies are in fact functionally associated with diverse CCAs. A series of recent studies using huge sample sizes (N > several hundred) of young adults showed that associations between individual aspects of cognition and regional gray matter structure were generally low 16 . Moreover, our previous study on simple processing speed involving several hundred subjects showed that performance was positively correlated with widespread regional white matter volume (rWMV) across different simple processing speed tasks; furthermore, the strengths of the associations were generally low and no single area showed significant specific correlations between rWMV and simple processing speed 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronotype‐specificity refers to individual preferences in sleep and wakefulness that reflect endogenous, self‐sustained genetic dispositions (Roenneberg & Merrow, ). Chronotypes have been found to be associated with differences in white matter integrity and gray matter density (Rosenberg, Maximov, Reske, Grinberg, & Shah, ; Takeuchi et al, ). Additionally, chronotype‐specific cerebral responses to language processing and attention also have been found (Reske, Rosenberg, Plapp, Kellermann, & Shah, ; Rosenberg, Reske, Warbrick, & Shah, ).…”
Section: Discussionmentioning
confidence: 99%